The Case for 'Benevolent' Mobile Apps - Sultan, Fareena; Urban, Glen (MIT Sloan Management Review, 2015)
Smartphones make up an increasing share of mobile devices, and mobile apps are among smartphones' most popular features. The all-time cumulative total of mobile app downloads stood at 37 billion at the end of 2011, and showed dramatic growth in 2012. Mobile app downloads more than doubled that year, resulting in a new cumulative total of 83 billion mobile app downloads. For companies, apps provide ample revenue opportunities. Mobile advertising has seen triple-digit percentage growth each year since PricewaterhouseCoopers began capturing this data in 2010. Yet some people have doubts about the effectiveness and viability of mobile advertising and believe that apps are a better medium. Authors Glen L. Urban and Fareena Sultan think one of the most effective uses of mobile media will be apps that are designed to build trust. They call these "benevolent" apps because the apps' value is not directly tied to selling products but rather to advancing consumers' interests and helping them solve problems or make decisions. One example is the Sea Tow app, offered by Sea Tow Service International, headquartered in Southold, New York, which provides emergency towing and rescue services for boaters in the United States, the Caribbean and Europe. The free app supports boaters' navigation needs by providing information about local tide tables, detailed marine weather forecasts, GPS coordinates and bearing, and speed. Urban and Sultan observe that a growing number of organizations, including well-known companies, have come forth with their own benevolent apps in which selling products takes a backseat to providing information and gaining trust. The authors present findings from two studies (one at Liberty Mutual Insurance and the other at Suruga Bank in Japan) showing that benevolent mobile apps that try to help consumers in decision making can positively impact consumers' perception of a brand, as well as their willingness to consider the brand and their preference for it.